PERCEPCIONES ECONÓMICAS POR EL FENÓMENO DE LA MIGRACIÓN VENEZOLANA HACIA COLOMBIA (2022)
A few decades ago, the economy in Venezuela was one of the best in Latin America, but now its economy is in total imbalance, this due to the fall in the price of the Bolivar in the foreign exchange market, along with the lack of payment of the country’s foreign debt. That and other national problems have caused many of its citizens to migrate to Colombia. The arrival of migrants has caused both good and bad comments by citizens and national and international entities, based on the Colombian economy and the uncertainty between a strong economic, or simply a severe decline.National and international entities such as the National Administrative Department of Statistics (DANE), Migration Colombia, International Monetary Fund (IMF), Brokerage House, Federation for Higher Education and Development (Fedesarrollo), Banks and the Press, have expressed their opinion about the effects of the inmigration of Venezuelans on the Colombian economy, trying to answer the question: Will the phenomenon of migration generate growth in productivity, investment and labor coverage or will the unemployment rate rise, generating economic echaustation? The hesitation is based on State spending in attention to the migrant population, when it could invest in the growth of the national economy.